Linking Melt Dynamics With Topological Phases and Molecular Structure of Sodium Phosphate Glasses From Calorimetry, Raman Scattering, and Infrared Reflectance - Mohanty, Chandi; Mandal, Avik; Gogi, Vamshi Kiran; Chen, Ping; Novita, Deassy; Chbeir, Ralph; Bauchy, Mathieu; Micoulaut, Matthieu; Boolchand, Punit (Frontiers in Materials, 2019)
A score of especially dry and homogeneous (Na2O)x(P2O5)100-x glass compositions over a wide range, 0 < x < 61%, are synthesized and examined in Modulated-DSC, Raman scattering, Infrared Reflectance and Molar volume experiments. The glass transition temperature variation, Tg(x) displays three regimes; at low x (0 < x < 15%), Na serves as a network modifier. At higher x, 15% < x < 50%, Na serves as a network former, as chains of Q2 species steadily grow and Tg(x) increases. In this regime, we observe a square-well like, thermally reversing window, bordered by abrupt rigidity transition near, xr = 37.5% and stress transition, near xs = 46.0% defining the Intermediate Phase (IP). The rigidity transition near xr = 37.5% occurs near the percolation of rigidity predicted by the Coarse Graining model. Variations of melt fragility index, m(x), established from complex Cp measurements show m(x =0) to be 15(1), and to increase monotonically with x to display a square-well-like fragility window (m < 20) in the 37.5(3)% < x < 46.0(2)% range, a range which coincides with the reversibility window. These results show that melt dynamics encode glass topological phases. At still higher x (> 50%), Tg(x) mildly decreases with increasing x, as pyrophosphate units decouple from the backbone and glasses segregate. Raman scattering measurements show that the fraction of the local structural species, f(Q3(x)), f(Q2(x)) and f(Q1(x)) track the mean-field behavior based on glass stoichiometry (x), as noted earlier from 31P NMR experiments. Raman scattering also shows that the Q2 structural species always display a triad of modes, a majority mode and two satellite modes that serve as topological defects. For the two highest frequency optic modes, Infrared specular reflectance measurements show that the frequency difference between the Longitudinal Optic (LO) and Transverse Optic (TO) response displays a global minimum in the IP. The local minimum of molar volumes, a global minimum in the LO-TO mode splitting, a fragility window that coincides with the reversibility window, each observation provides persuasive evidence of the singular role of the IP in present glasses.